Micro-computed tomographic evaluation of a new system for root canal filling using calcium silicate-based root canal sealers - Mario Tanomaru-Filho; Fernanda Ferrari Esteves Torres; Jader Camilo Pinto; Airton Oliveira Santos-Junior; Karina Ines Medina Carita Tavares; Juliane Maria Guerreiro-Tanomaru (Restorative Dentistry & Endodontics)
ObjectivesThis study evaluated by using micro-computed tomography (micro-CT) the filling ability and sealer apical extrusion promoted by a new Sealer Injection System (SIS; Angelus) with side openings needle, in comparison with the conventional injection system, associated with a new ready-to-use calcium silicate-based sealer (Bio-C Sealer).Materials and MethodsAcrylic resin models containing a main curved artificial canal and 3 simulated lateral canals in apical, middle and cervical thirds were used. The main root canals were prepared using a rotary system up to size 35.05. The canals were filled with Bio-C sealer by using a single cone technique and the conventional delivery system or SIS. Samples were scanned in micro-CT. The percentage of voids throughout the entire extension of the main root canal and in each third of the lateral canals, besides the apical extrusion of the sealer was calculated. Data were submitted to t-test (p < 0.05).ResultsThere was no difference between both systems in the main root canals filling. Although the volume percentage of voids was similar in the apical and middle thirds of lateral canals, SIS had the greatest filling ability of the cervical third lateral canal. Moreover, the conventional system showed the highest apical extrusion of the sealer.ConclusionsThe conventional and SIS obturation systems had an appropriate filling ability of the main root canal. SIS had the best filling of the cervical third of the lateral canals, besides lower sealer apical extrusion, suggesting its clinical indication.